2012
DOI: 10.1055/s-0039-3401654
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variations in the Anatomy of Caecum and Appendix - A Cadaveric Study

Abstract: Background : Appendicitis is one of the most common clinical conditions that require emergency surgery. Variations in anatomical location of appendix can result in different clinical presentations. Anatomical and topographical variations of the caecum are also known to occur. Anatomical variations in caecum have been observed along with the appendix in this study. Aims: To study the variations in the size, shape, position and arterial supply of the caecum and appendix in individuals of different sex and age, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In a laparoscopic study by Gupta et al [11] in New Delhi, the mean length and width of the appendix were reported 6.8 cm and 0.87 cm in children, while these values were 5.25 cm and 0.72 cm in adult. The length of the Indian cadavers ranges between 5.9 and 10.21 and the values obtained for thickness ranges from 0.46 cm to 0.7 cm [2,3,8,22]. In the present study, the appendix length and width were longer than those in Indian population (12.17 mm and 0.46 mm, respectively).…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…In a laparoscopic study by Gupta et al [11] in New Delhi, the mean length and width of the appendix were reported 6.8 cm and 0.87 cm in children, while these values were 5.25 cm and 0.72 cm in adult. The length of the Indian cadavers ranges between 5.9 and 10.21 and the values obtained for thickness ranges from 0.46 cm to 0.7 cm [2,3,8,22]. In the present study, the appendix length and width were longer than those in Indian population (12.17 mm and 0.46 mm, respectively).…”
Section: Discussionsupporting
confidence: 42%
“…There was remarkable variation of appendix position in different regions of Asia. The most frequent position of the appendix was found retrocaecal in India [3,15,22,25] ranging from 55.5% to 68%. The most common location of the vermiform appendix was retroileal in Thai population [5], while pelvic was a predominant position in Iranian cadavers [9,10,24], which was inconsistent with our finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adult incidence is 0.00009% in south-east Asian countries; however it varies from 0.09-4% in Indian population. [4][5][6] Discrete existence of sub-hepatic caecum and dilated with looped sigmoid colon has been described by many authors. [3][4][5][6] The aim of this report is to highlight co-existence of subhepatic caecum and dilated with looped sigmoid colon at variant position in abdominal cavity.…”
Section: Introductionmentioning
confidence: 99%